Chemical Profiling and Antifungal Activity of Volatile Oil of Cupressus torulosa against Pathogenic Fungi - Bhandari, Ujjwal (International Journal of Pharmaceutical & Biological Archive, 2016)
Chemical Profiling and Antifungal Activity of Volatile Oil of Cupressus torulosa against Pathogenic Fungi